How to author a picture gallery. (November 2019) - Caple, Helen; Knox, John S
Picture galleries offer photojournalism an opportunity to shine. Despite the considerable technological advances of recent decades, picture galleries typically fail to realise their potential for storytelling; rather they present an incohesive series of image–caption complexes collected under a headline. Here, we offer a set of guidelines regarding the sourcing, selection and sequencing of compelling images coupled with agile writing of leads and captions that complement the kind of visual story being told. Such investment in the authoring of picture galleries creates opportunities to provide readers with an engaging and more memorable experience.